Posterior cervical full-endoscopic technique for the treatment of cervical spondylotic radiculopathy with foraminal bony stenosis: A retrospective study - Shi, Meng; Wang, Cong; Wang, Huihao; Ding, Xiaoqing; Feng, Juntao; Zhou, Lin; Cai, Yuwei; Yu, Zhongxiang (Frontiers in Surgery, 2023)
Objective: In the treatment of cervical spondylotic radiculopathy (CSR), spinal endoscopy has been developed vigorously in the past 30 years. However, its effectiveness and subsequent problem of cervical spine stability have always been the controversial hotspots. This study aims to conduct a retrospective study using posterior cervical full-endoscopic technique for the treatment of CSR with foraminal bony stenosis, and evaluate its clinical effect and application value. Methods: All 22 patients treated for CSR with foraminal bony stenosis using posterior cervical full-endoscopic technique were analyzed since Dec 1, 2016, to Apr 30, 2020. The data collection included operation time, length of stay, wound healing, surgical complications, visual analog scale (VAS), Japanese Orthopaedic Association (JOA) scores, intervertebral foramen diameter, intervertebral foramen area and cervical instability. The relevant indicators were observed on admission, at postoperative 1 week and 3 months, and at the last follow-up. Results: The operation time was 141.6 ± 13.7 minutes. The length of stay was 6.0 ± 2.5 days. VAS and JOA at different time points after operation were decreased compared with before operation (p<0.05). There were no statistical differences between VAS or JOA at different postoperative time points (p>0.05). The height, anteroposterior diameter and area of intervertebral foramen after operation were significantly increased compared with before operation (p<0.05). Conclusion: Posterior cervical full-endoscopic technique shows the advantages of smaller invasion, faster recovery, significant effectiveness and fewer complications in our study. Meanwhile, it has little influence on the ROM and stability of the cervical spine. Therefore, it is a minimally invasive, safe and effective surgical method for the treatment of CSR with foraminal bony stenosis.